Cancer risk in dialyzed patients with and without diabetes. (April 2020) - Pladys, Adélaïde; Defossez, Gautier; Lemordant, Pierre; Lassalle, Mathilde; Ingrand, Pierre; Jacquelinet, Christian; Riou, Christine; Bouzillé, Guillaume; Van Hille, Pascal; Vigneau, Cécile; Cuggia, Marc; Bayat, Sahar
Abstract: Background: The risk of cancer is higher in patients with renal diseases and diabetes compared with the general population. The aim of this study was to assess in dialyzed patients, the association between diabetes and the risk to develop a cancer after dialysis start. Methods: All patients who started dialysis in the French region of Poitou-Charentes between 2008 and 2015 were included. Their baseline characteristics were extracted from the French Renal Epidemiology and Information Network and were linked to data relative to cancer occurrence from the Poitou-Charentes General Cancer Registry using a procedure developed by the INSHARE platform. The association between diabetes and the risk of cancer was assessed using the Fine & Gray model that takes into account the competing risk of death. Results: Among the 1634 patients included, 591 (36.2 %) had diabetes and 91 (5.6 %) patients developed a cancer (n = 24 before or at dialysis start, and n = 67 after dialysis start). The risk to develop a cancer after dialysis initiation was lower in dialyzed patients with diabetes than without diabetes (SHR = 0.54; 95 %CI: 0.32-0.91). Moreover, compared with the general population, the cancer risk was higher in dialyzed patients without diabetes, but not in those with diabetes. Conclusion: The risk of developing a cancer in the region of Poitou-Charentes is higher in dialyzed patients without diabetes than with diabetes.